Effects of Arbuscular Mycorrhiza and Phosphate Fertilizer on Phosphorus Uptake of Vetiver Using Nuclear Technique - Sombun Techapinyawat; Pannee Pakkong; Poonpilai Suwanarit; Pattarawadee Sumthong (Agriculture and Natural Resources, 2002)
This experiment was done in 4×4 factorial treatment combinations with 4 replications in completely randomized design to evaluate the effects of 3 species of arbuscular mycorrhizal fungi : Acaulospora scrobiculata, Glomus aggregatum and Glomus sp. combined with phosphate fertilizer on phosphorus uptake of vetiver (Vetiveria zizanioides L. Nash). Four levels of superphosphate 0, 30, 60 and 90 kg P2O5 / ha (labels with P-32) were used. Vetiver height was increased when phosphate fertilizer was supplied, whereas the tiller number and biomass did not show any responses when P-fertilizer was applied. Comparing the different types of mycorrhizal treatments, A. scrobiculata significantly increased vetiver growth in terms of height and biomass, while the number of tillers per plant were not affected. The highest number of tiller per plant was found in G. aggregatum treated plant. Arbuscular mycorrhizal fungi significantly increased P-concentration, P-uptake, % P derived from fertilizer and P-availability in vetiver. At 60 kg P2O5 / ha level of application, the highest percentage of P derived from fertilizer (0.545%), P-availability (0.037%FPU ), and total P-uptake (6.25mg/clump) were obtained from A.scrobiculata , whereas G. aggregatum treatments with no P-supplied gave the greatest P-concentration (0.104%). Increasing phosphate fertilizer up to 90 kg P2O5 / ha, resulted in non-significant changes of P-uptake and P-availibility in VA mycorrhizal plants.